Diurnal changes in shoot water dynamics are synchronized with hypocotyl elongation in Arabidopsis thaliana - Ishikawa, H.; Sato-Nara, K.; Takase, T.; Suzuki, H. (Informa UK Limited, 2013)
We recently demonstrated the circadian clock modulated water dynamics in the roots of a small model plant, Arabidopsis thaliana, by the Nuclear Magnetic Resonance (NMR) microimaging technique. Our developed technique was able to visualize the water distribution that depended on differences in the 1H signal among region in the shoot, such as the shoot apex, the hypocotyl and the root shoot junction. Water content in the shoot increased during periods of light in comparison with dark periods, and continued through the early stage of seedling growth until the dark period. When the water content changed, elongation and/or movement occurred in the hypocotyl, and these events were synchronized. The water dynamics of the shoot also displayed an opposite phase with the root water dynamics.